KEWENANGAN YURIDIS MAHKAMAH PELAYARAN BERDASARKAN PERATURAN PERUNDANG-UNDANGAN (Lex Jurnalica, 2018)
AbstractThis research uses a normative juridical approach to determine the existence of the Admiralty Court in Indonesia.The Admiralty Court is an Institution which is born from the mandate of Law Number 21 of 1992 on Shipping. The main duties and functions of this institution are to investigate whether there is negligence carried out by the ship's captain or ship’s officer, in addition the Admiralty Court also decides on administrative sanctions for the ship's captain or ship’s officer. However, related to losses suffered by third parties due to ship accidents, the Admiralty Court does not have juridical authority. So, even though the Admiralty Court has been around for a long time, the AmiraltyCourt is only an executive institution, so that the juridical authority is not as wide as other judicial institutions.. Keywords : admiralty, admiralty court, ship, law sea AbstrakPenelitian ini menggunakan pendekatan yuridis normatif untuk mengetahui eksistensi Mahkamah Pelayaran di Indonesia. Mahkamah Pelayaran merupakan Lembaga pemerintah yang lahir dari amanat Undang-Undang Nomor 21 Tahun 1992 tentang Pelayaran. Tugas pokok dan fungsi Lembaga ini untuk menyelediki ada tidaknya kelalaian yang dilakukan nakhoda atau perwira kapal, selain itu Mahkamah Pelayaran juga memutuskan sanksi administratif bagi nakhoda atau perwira kapal. Namun demikian, terkait kerugian yang dialami pihak ketiga akibat kecelakaan kapal, Mahkamah Pelayaran tidak mempunyai kewenangan yuridis. Sehingga, meskipun Mahkamah Pelayaran sudah ada sejak lama, namun mahkamah pelayaran hanyalah Lembaga eksekutif, sehingga kewenangan yuridis yang dimiliki tidak seluas Lembaga peradilan lainnya. Kata kunci : mahkamah pelayaran, hukum laut, kapal